2019
DOI: 10.1101/702068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microarray Gene Expression Dataset Re-Analysis Reveals Variability in Influenza Infection and Vaccination

Abstract: 2Influenza, a communicable disease, affects thousands of people worldwide. Young children, 3 elderly, immunocompromised individuals and pregnant women are at higher risk for being 4 infected by the influenza virus. Our study aims to highlight differentially expressed genes in 5 influenza disease compared to influenza vaccination. We also investigate genetic variation 6 due to the age and sex of samples. To accomplish our goals, we conducted a meta-analysis 7 using publicly available microarray expression… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…We used a systems vaccinology approach to study the response to influenza vaccination and found that both young and older subjects develop an antibody response to immunization using different immunometabolic paths. Our study suggests that the main variable in response to influenza vaccination is age (Figure 1c), a finding that is in agreement with previous studies (Furman & Jojic, 2013; Haschemi & Kosma, 2012; Kennedy & Ovsyannikova, 2016; Nakaya et al, 2011; Rogers et al, 2019; Thakar et al, 2015; Tsang et al, 2014; Voigt et al, 2019). The differences we observed reflect a differential metabolic baseline of young versus older adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We used a systems vaccinology approach to study the response to influenza vaccination and found that both young and older subjects develop an antibody response to immunization using different immunometabolic paths. Our study suggests that the main variable in response to influenza vaccination is age (Figure 1c), a finding that is in agreement with previous studies (Furman & Jojic, 2013; Haschemi & Kosma, 2012; Kennedy & Ovsyannikova, 2016; Nakaya et al, 2011; Rogers et al, 2019; Thakar et al, 2015; Tsang et al, 2014; Voigt et al, 2019). The differences we observed reflect a differential metabolic baseline of young versus older adults.…”
Section: Discussionsupporting
confidence: 93%
“…Longitudinal studies showed consistent transcriptomic and microRNA signatures of influenza vaccination across seasons in the same cohort (Nakaya et al, 2015). One of the most consistent findings is that age is an important contributor to influenza vaccine response (Furman & Jojic, 2013; Haschemi & Kosma, 2012; Nakaya et al, 2011; Rogers et al, 2019; Tsang et al, 2014). We previously investigated the transcriptomic signature of immune response to influenza vaccination and found that a mitochondrial biogenesis signature was associated with vaccine antibody response (Thakar et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Results have identified around 1000 differentially expressed genes when results were filtered by disease factor, and gene enrichment analysis, with statistically significant disease-age interactions. Genes included innate immune response, viral process, defense response to virus, hematopoietic cell lineage and NF-kB signaling pathway [ 49 ]. A mitochondrial signature of young and old influenza vaccine responders has identified genes and proteins controlling mitochondrial biogenesis and pathways of oxidative phosphorylation [ 50 ].…”
Section: Aging Decreases Influenza Vaccine-specific Antibody Responsementioning
confidence: 99%
“…Expression profiling through microarray analysis is a valuable high-throughput tool that allows researchers to determine quantitative gene expression for a large number of mRNA transcripts 1 . Recent meta-analyses of publicly available microarray data have proven to be beneficial for identifying novel contributing genes for several diseases including influenza 2 , atherosclerosis 3 , chronic pain 4 , cancer 5, 6 , and Parkinson’s disease 7 . To date, however, few studies have used this approach to identify novel gene targets in the Alzheimer’s disease (AD) brain.…”
mentioning
confidence: 99%